INFLUENCE OF PRODUCT ATTRIBUTES AND VARIETY SEEKING ON BRAND SWITCHING BEHAVIOR OF XIAOMI SMARTPHONE USERS - Faishal Ardiansyah; Nuruni Ika Kusuma Wardhani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The high number of smartphone users in Indonesia has made the country a potential target market for smartphone companies. This makes consumers in this sector more selective in choosing a smartphone brand. This selective behavior of consumers is a sign that there can be brand switching behavior by consumers due to unfulfilled consumer needs and desires. This study aims to determine the effect of Product Attributes and Variety Seeking on Brand Switching Behavior of Xiaomi smartphone by UPN Veteran East Java students. This study uses a quantitative method using 81 people as a research sample. The number of respondents was determined using a non-probability sampling method with purposive sampling technique. The data collection method was carried out through conventional questionnaire distribution and measured using a Likert scale. The analytical tool used in this research is Partial Least Square (PLS). The results of this study indicate that the variables of product attributes and variety seeking have a significant influence on brand switching of Xiaomi smartphone brands by students of the National Development University "Veteran" East Java.